2014
DOI: 10.1038/aps.2014.72
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic analysis of simvastatin and fenofibrate intervention in high-lipid diet-induced hyperlipidemia rats

Abstract: A series of potential biomarkers including tyrosine, creatinine, linoleic acid, β-hydroxybutyric acid and ornithine have been identified by metabolomic profiling, which may be used to identify the metabolic changes during hyperlipidemia progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 44 publications
(52 reference statements)
1
33
1
1
Order By: Relevance
“…This reduction in plasma urea concentration may be associated with a lower protein catabolism or alternatively with an increase in the efficiency of nitrogen utilization [37] when feeding a high-fat, high-fibre diet. Similarly to our results, hyperlipidaemia induced by a high-fat diet was associated with a lower plasma level of tyrosine in rats [38,39]. Tyrosine is formed from the essential amino acid phenylalanine, which could explain the lower plasma level of this latter amino acid in pigs fed the HF diet than in pigs fed the LF diet [40].…”
Section: Discussionsupporting
confidence: 89%
“…This reduction in plasma urea concentration may be associated with a lower protein catabolism or alternatively with an increase in the efficiency of nitrogen utilization [37] when feeding a high-fat, high-fibre diet. Similarly to our results, hyperlipidaemia induced by a high-fat diet was associated with a lower plasma level of tyrosine in rats [38,39]. Tyrosine is formed from the essential amino acid phenylalanine, which could explain the lower plasma level of this latter amino acid in pigs fed the HF diet than in pigs fed the LF diet [40].…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, a significant increase in the atrial blood lactate level was observed during acute AF (van Bragt et al , ). Fenofibrate was reported to significantly decrease the level of BOH in high‐lipid diet rats (Xu et al , ). We demonstrated that AF induced a marked increase in the circulating lactate, AcAc, BOH and TKB levels in rabbits subjected to rapid‐pacing for 1 week.…”
Section: Discussionmentioning
confidence: 99%
“…; Ozório ; Xu et al . ). In general, although blood glucose concentration of fish is in a dynamic equilibrium due to the regulation by the nervous and endocrine systems, but it is quite easy to change (Imsland et al .…”
Section: Regulation Of L‐carnitine On Nutrients Metabolism In Aquaticmentioning
confidence: 97%